(468) تقييم وأختيار الاستثمارات الصناعية(الجزء الأول) Evaluating and Selecting Industrial Investments (Part I) - صالح مغيب (معهد التخطيط القومي, 2026)
تتناول هذه المذكرة الأسس العلمية والعملية لعملية "تقييم واختيار الاستثمارات الصناعية"، مبرزةً أهمية هذه الدراسات كأداة للمفاضلة بين البدائل لضمان تحقيق أقصى عائد مالي واجتماعي، ويحلل البحث دوافع الاهتمام بالتنمية الصناعية في الدول النامية كسبيل لرفع الدخل القومي وتصحيح الاختلالات الهيكلية الناتجة عن الاعتماد المفرط على الزراعة، مع تسليط الضوء على التحديات الديمغرافية مثل الانفجار السكاني وضرورة خلق فرص عمل حقيقية لاستيعاب القوى العاملة المتزايدة وتطوير مهاراتها لمواكبة التقدم التكنولوجي السريع ،كما يستعرض الجوانب الفنية للتقييم، مستعرضاً كيفية قياس الآثار المباشرة وغير المباشرة للمشروعات على الاقتصاد القومي، خاصة فيما يتعلق بـ "ميزان المدفوعات" ووفورات النقد الأجنبي عبر استراتيجيات إحلال الواردات، ويستعرض البحث الإطار المؤسسي والتشريعي في مصر آنذاك، مبيناً دور الهيئات المتخصصة مثل "الهيئة العامة للاستثمار" و"جهاز التعاون الدولي" في جذب رؤوس الأموال العربية والأجنبية وتوفير الضمانات اللازمة للمستثمرين، مؤكداً في الختام على أن التخطيط العلمي السليم هو الضمانة الوحيدة لتحويل الاستثمارات من مجرد أعباء مالية إلى قاطرة حقيقية للتنمية المستدامة. This memorandum addresses the scientific and practical foundations of the process of "evaluating and selecting industrial investments," highlighting the importance of these studies as a tool for choosing between alternatives to ensure the achievement of maximum financial and social returns. The research analyzes the motives for interest in industrial development in developing countries as a means to raise national income and correct structural imbalances resulting from excessive dependence on agriculture, while highlighting demographic challenges such as the population explosion and the need to create real job opportunities to absorb the growing workforce and develop its skills to keep pace with rapid technological progress. It also reviews the technical aspects of evaluation, reviewing how to measure the direct and indirect effects of projects on the national economy, especially with regard to the "balance of payments" and foreign exchange savings through import substitution strategies. The research reviews the institutional and legislative framework in Egypt at that time, explaining the role of specialized bodies such as the "General Authority for Investment" and the "International Cooperation Authority" in attracting Arab and foreign capital and providing the necessary guarantees for investors, stressing in conclusion that sound scientific planning is the only guarantee for transforming investments from mere financial burdens into a real engine for sustainable development.